The Role of the Immune Phenotype in Tumor Progression and Prognosis of Patients with Mycosis Fungoides: A Quantitative Immunohistology Whole Slide Approach - Natallia Aulasevich; Maximilian Haist; Sebastian Försch; Beate Weidenthaler-Barth; Volker Mailänder (Cells, 2022)
Background and objectives: Mycosis fungoides (MF) is the most common type of cutaneous T-cell lymphomas, characterized by mature, skin-tropic CD4+ T-helper cells. In order to study the immune tumor microenvironment in MF patients, we performed immunohistochemical stains on MF biopsies, digitized whole-slide tissue sections, and performed quantitative analysis of the different immune cell subsets to correlate tissue parameters with the clinical data of patients, such as progression-free survival or overall survival. Patients and methods: Overall, 35 patients who were treated between 2009 and 2019 and for whom one or more paraffin tissue blocks were available have been included in the present study (58 tissue specimens in total). Conventional immunohistochemistry stains for CD3, CD4, CD8, CD20 and CD30 were used for the analysis of the immune phenotype, and quantitative analysis was performed using QuPath as a quantitative digital pathology tool for bioimage analysis of whole slides. Results: Analysis of tissue parameters for prognostic significance revealed that patients with a stronger infiltration by CD8+ lymphocytes within the tumor cell compartment had a higher risk of disease progression (p = 0.031) and showed a shorter progress-free survival (p = 0.038). Furthermore, a significant association of the percentage of CD30+ cells (median: 7.8%) with the risk of disease progression (p = 0.023) and progression-free survival (p = 0.023) was found. In relation to the clinical features of our patient cohort, a higher risk of disease progression (p = 0.015) and a shorter progression-free survival (p = 0.032) for older patients (>61 years) were observed. Conclusions: Our results demonstrated the prognostic relevance of large-cell transformation in mycosis fungoides and its strong association with the presence of CD30+ lymphocytes. Unlike previous reports, our study suggests an adverse prognostic role for CD8+ T cells in patients with mycosis fungoides. Moreover, our data indicate that the immune phenotype within the tumor microenvironment shows strong temporal heterogeneity and is altered in the course of tumor progression.